Effect of Sargassum aquifolium Juice on Lipid Profile and Inflammatory Cytokines in Hypercholesterolemic Rats - Muhamad Firdaus; Retno Tri Astuti; Yoga Dwi Jatmiko; Herlina Pratiwi (International Journal of Food Science)
Obesity, a global health burden, is marked by increased lipid levels and chronic inflammation. Sargassum aquifolium is a brown seaweed rich in bioactive compounds that may improve lipid profile and inflammation. This study is aimed at evaluating the potential of S. aquifolium juice in modulating lipid profiles and inflammatory responses in hypercholesterolemic rats. High-performance liquid chromatography–high-resolution mass spectrometry (HPLC–HRMS) analysis identified bioactive compounds, including niacin, whose potential antihypercholesterolemic effect was supported by in silico PASS prediction. Male Wistar rats were divided into five groups: normal, hypercholesterolemic, and hypercholesterolemic rats fed S. aquifolium juice once, twice, and thrice daily for 120 days. The results showed that administration of S. aquifolium juice, especially twice daily, significantly reduced TG and total cholesterol, raised HDL, lowered AI and malondialdehyde (MDA), and modulated IL-4, TNF-α, and IL-1β expression by CD4+ cells. In hypercholesterolemic rats, IL-4 expression was lower, and TNF-α and IL-1β were higher than normal. However, S. aquifolium juice increased IL-4 and decreased TNF-α and IL-1β, suggesting an immunomodulatory effect. Niacin in S. aquifolium juice may improve lipid profiles and suppress inflammatory cytokines via NF-κB inhibition and NLRP3 inflammasome modulation. Overall, these findings highlight the potential of S. aquifolium juice as a natural antihypercholesterolemic agent for managing hypercholesterolemia and preventing atherosclerosis, though further larger scale investigations are needed.